Rancang Bangun Game Adventure 3D Edukasi Sampah Organik dan Non-Organik: Design and Build an Educational 3D Adventure Game on Organic and Non-Organic Waste - Nur Aieni, Ika; Taurusta, Cindy; Sumarno (Technomedia Journal, 2024)
This research aims to design and develop an Educational 3D Adventure Game as an informative tool for organic and non-organic waste. The development method employed is MDLC (Multimedia Development Life Cycle), encompassing Concept, Design, Material Collecting, Assembly, Testing, and Distribution stages. The game was successfully created for the Android platform using Unity3D.The testing results, involving 22 respondents from Gedang Rowo Village, demonstrate a positive response with an approval rate of 90%. Media experts' evaluation reached 68%, while content experts provided a 100% approval rate. These findings indicate that "TrashHero" has effectively become an engaging and interactive information medium regarding organic and non-organic waste.Utilizing the Likert scale, the conclusion drawn from the testing affirms that "TrashHero" has achieved a remarkably high level of success. Therefore, this game is considered an effective educational tool for conveying information about waste while providing an interactive experience for users.